2013
DOI: 10.1002/jhet.1548
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Synthesis of Dibenzoxazepines

Abstract: Dibenzo[b,f][1,4]oxazepine derivatives were synthesized in good yields and short reaction times by the reaction of 2‐chlorobenzaldehydes and 2‐aminophenoles in basic conditions under microwave irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…2-Nitrodibenzo[b,f][1,4]-oxazepines 1 b-1 g were easily prepared from 2-chloro-5-nitrobenzaldehyde and various 2-aminophenols. [14] It is worth noting that in all scope reactions, CO 2 served as the protecting gas and did not participate in the annulation. During the [2 + 2] annulation, it was observed that the presence of an electron-donating substituent methyl (3 ea) on the N-aryl group greatly benefited the reaction, resulting in a yield of 67 %.…”
Section: Resultsmentioning
confidence: 99%
“…2-Nitrodibenzo[b,f][1,4]-oxazepines 1 b-1 g were easily prepared from 2-chloro-5-nitrobenzaldehyde and various 2-aminophenols. [14] It is worth noting that in all scope reactions, CO 2 served as the protecting gas and did not participate in the annulation. During the [2 + 2] annulation, it was observed that the presence of an electron-donating substituent methyl (3 ea) on the N-aryl group greatly benefited the reaction, resulting in a yield of 67 %.…”
Section: Resultsmentioning
confidence: 99%
“…Various 2-chlorobenzaldehydes 1 and 2-aminophenols 2 were employed and corresponding substituted dibenzo [b,f] [1,4] oxazepine derivatives were obtained in high yields (Scheme 5). The superiority of the ultrasound irradiation over microwave irradiation [15] The structure of the products was investigated by 1 H NMR, 13 …”
Section: Resultsmentioning
confidence: 99%
“…Limited attention has been given to the synthesis of this structure including [7]: i) A two-step protocol involving etherification and reductive cyclization of 1-halo-2-nitrobenzene and salicylaldehyde (Scheme 2a) [12,13], ii) A two-step method involving imination and etherification of 2-aminophenol with 2-halobenzaldehyde (Scheme 2b) [14,15]. Etherification of these reactions proceed by an intramolecular nucleophilic displacement of nitro, fluoro, or chloro groups in high boiling polar solvents such as dimethyl sulfoxide at high temperature (Over 100 °C) with long reaction time.…”
Section: Introductionmentioning
confidence: 99%
“…Various 2-chlorobenzaldehydes 1 and 2-aminophenols 2 were employed and corresponding substituted dibenzo [b,f] [1,4] oxazepine derivatives were obtained in high yields (Scheme 5). The superiority of the ultrasound irradiation over microwave irradiation [15] in the synthesis of dibenzo [b,f] [1,4] oxazepine derivatives is low reaction temperature and operational simplicity of the ultrasound irradiation technique. The structure of the products was investigated by 1 H NMR, 13…”
Section: Resultsmentioning
confidence: 99%